GIS and Multi-criteria Analysis for School Site Selection (Study Case: Malacca Historical City) - Anjang Ahmad, Mustaffa Bin; Bahiah, B.; Rasib, A. W.; Saifullizan, M. B. (International Journal of Integrated Engineering, 2021)
Abstract: A set of school suitability map would be very useful for education planners when making a complex decision within a short period of time. This study will utilize both spatial and non-spatial parameters to establish a systematic site selection process for primary schools in Melaka Tengah District. It was carried out by using Geographic Information System (GIS) and Multi-criteria Decision Analysis (MCDA). Three analysis namely demographic, safety and constrain analysis were used to identify the potential sites. Then accessibility analysis, using expertise and public opinion were used to further analyze the potential site. The resulted map showed 54.2% of the total area is highly not suitable, leaving 46% suitable for school sitting. The final safety model output was compared with field verification data from State Education Department (JPN Melaka) and Malacca Historical City Council (MBMBB)..